Preservation of Serratia marcescens by High-Vacuum Lyophilization - Dewald, Robert R. (1966)
Water-washed Serratia marcescens (ATCC strain 14041) cells were lyophilized in an all-glass system capable of evacuation to pressures of less than 5 × 10(-6) torr. Lyophilization at the lowest pressures resulted in 50 to 65% survival for unstabilized washed organisms compared with 10 to 20% when the cells were lyophilized at pressures of about 2.5 × 10(-2) torr. At the latter pressures, 45 to 65% survival was obtained when NaCl or Naylor-Smith stabilizer was added to the cell suspensions before lyophilization. However, the stabilizers failed to increase significantly the levels of survival compared with water suspension when cells were lyophilized at pressures less than 10(-5) torr. The high survival rates obtained by the high-vacuum technique may be attributed to the reduction of traces of molecular oxygen which has been reported to be destructive of the dried bacteria. Survival of unstabilized dried S. marcescens after 1-day storage increased markedly with decreasing sealing pressure. Under the highest vacuum attained, survival of the dried bacteria was not impaired by storage for up to 1 month at Dry Ice temperatures; at higher temperatures, viability losses occurred. Exposure of the dried unstabilized bacteria to dry air resulted in rapid viability loss. The inactivation could be stopped almost immediately by evacuation to pressures of less than 10(-5) torr, but the evacuation failed to reverse the viability losses that occurred during exposure.